PERAN ARABIC CLUB DALAM MENINGKATKAN MOTIVASI DAN KEMAMPUAN BAHASA ARAB SISWA SMA AL ISLAM 1 SURAKARTA - Fatimah Marthalia Putri; Yunanto, Al Khanza Abel; Azzahrani, Syafina; Iffah, Ummu Jatsya; Khotimah, Putri Chusnul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low interest and limited Arabic language proficiency in non-boarding public schools are often caused by the lack of a supportive language environment and limited extracurricular activities. This study aims to describe the coaching patterns, teaching material innovations, and the contribution of the Arabic Club in improving students’ motivation and Arabic language skills at SMA Al Islam 1 Surakarta. This research employed a descriptive qualitative approach using a case study method. Data were collected through observation, interviews, and documentation and analyzed using the interactive model of Miles and Huberman. The findings show that the Arabic Club implements a flexible and student-centered learning approach through conversation practice, language games, and contextual writing exercises. Club membership fluctuated from 35 members in 2018–2020 to only 1 member in 2024, but increased again in 2025 through interest-based recruitment. In addition, the supervisor developed internal teaching materials in the form of a dialogue book titled Al-Hiwārāt al-Mufīdah li Taṭbīq al-Lughah al ‘Arabiyyah. These findings indicate that adaptive and innovative coaching can enhance students’ motivation and participation in learning Arabic.